A Study on Injury Patterns among Motorcyclists Presenting to a Tertiary Care Hospital in South Kerala - Stalin, M; Paul , PM; Devassy, S; AT, Vaishnavi; Rajeev , VM (Journal of Indian Academy of Forensic Medicine, 2024)
High traffic levels on the road and the low costs of procurement and usage make motorcycles attractive in India. However, motorcycle  riders and passengers are more vulnerable to traffic accidents. The present study, which was conducted in a tertiary care hospital in South  Kerala, focused on injury patterns related to motorcycle accidents, including the factors associated with such accidents. The results found  that males (80%, 212) were more often victims of motorcycle accidents than females (20%, 53). The most affected age group was 20–39  years, at 41.5% (110). Most victims who came to the hospital had fractures (73.2%). Based on the fracture site, the head and neck areas  were the most affected (48.5%). Based on external injury, the head and neck areas were again the most affected (63.9%).
Keywords: Road traffic accidents; Injury pattern; Epidemiology